2020
DOI: 10.1186/s12978-020-00940-9
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preferences among couples in Nigeria: a cross sectional study

Abstract: Background: The persistently high and stalled total fertility in Sub-Saharan Africa, including in Nigeria, calls for new efforts towards fertility reduction. Most efforts on fertility desire in sub-Saharan Africa have focused either on individual men or women with little focus on couples as a unit of analysis. Moreover, the influences of different types of marriages in which couples reproduce have not been adequately explored. Therefore, this study examined fertility desires among couples in Nigeria. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
34
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 23 publications
8
34
0
2
Order By: Relevance
“…The odds of large family size desire were lesser among Christians than Muslims. These also concur with results from previous fertility studies [ 21 , 28 , 29 ]. The differences observed between Christians and Muslims could be due to variations in their dispositions to polygamy.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The odds of large family size desire were lesser among Christians than Muslims. These also concur with results from previous fertility studies [ 21 , 28 , 29 ]. The differences observed between Christians and Muslims could be due to variations in their dispositions to polygamy.…”
Section: Discussionsupporting
confidence: 93%
“…For both of men and women, regional differences between the South West and other regions were obvious. This has been the persistent patterns in several demographic and reproductive health indices in Nigeria [ 28 , 29 , 42 , 57 , 58 ]. Consequently, there have been repeated recommendations that intervention programmes be tailored to the peculiarities of each geo-political region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Rwanda, the majority of the population desired 0-3 children regardless of religion while in Kenya, Catholics and Protestants desired 0-3 children, whereas Muslims and Other Religions desired six or more children (Muhoza, 2019). In Nigeria, religiously homogamous couples had equal desires for the ideal number of children, whereas religiously heterogamous couples had a higher percentage where the husband desired higher fertility (Odusina, et al, 2020).…”
Section: Fertility Desires (In Total 5 Papers)mentioning
confidence: 99%
“…Studies have established that fertility preference is not stable and changes due to prevailing circumstances (Liefbroer, 2009;Trinitapoli & Yeatman, 2018). Furthermore, studies conducted in sub-Saharan Africa (SSA) including Ghana have identified a number of factors as predictors of high fertility preference (Ahinkorah et al, 2020;Kodzi et al, 2010;Odusina et al, 2020;Van Lith et al, 2013). Findings from these studies suggest positive relationship between fertility preference and actual fertility.…”
mentioning
confidence: 99%